Post-Traumatic Stress Disorder: The Relationship Between the Fear Response and Chronic Stress. (June 2017) - Maeng, Lisa Y; Milad, Mohammed R
Post-traumatic stress disorder (PTSD) is a disabling psychiatric condition that can develop following a physical, psychological, or sexual trauma. Despite the growing body of literature examining the psychological and biological factors involved in PTSD psychopathology, specific biomarkers that may improve diagnosis and treatment of PTSD have yet to be identified and validated. This challenge may be attributed to the diverse array of symptoms that individuals with the disorder manifest. Examining the interrelated stress and fear systems allows for a more comprehensive study of these symptoms, and through this approach, which aligns with the research domain criteria (RDoC) framework, neural and psychophysiological measures of PTSD have emerged. In this review, we discuss PTSD neurobiology and treatment within the context of fear and stress network interactions and elucidate the advantages of using an RDoC approach to better understand PTSD with fear conditioning and extinction paradigms.